THE ROLE OF SOCIAL STUDIES AND HISTORY LEARNING IN JUNIOR HIGH SCHOOL IN STRENGTHENING THE STUDENTS CHARACTER - Agung S., Leo (History Department, Semarang State University and Historian Society of Indonesia, 2015)
Nowadays, in Indonesia a variety of violence and moral degradation event still occur. The moral degradation phenomenon (among others) is indicated with the spread of violence, criminality, drug abuse, free sexual-intercourse and other misbehaviors. Multidimensional crisis and nation deterioration originates essentially in self-esteem, and failure in developing nationâs character education. Essentially, Social Science learning aimed to develop personal, social, and intellectual behavior. Thus, Social Science learning in Junior High Schools becomes a means and opportunity of strengthening the student characters such as sense of critical, discipline, environment awareness, social care, religious, having reading interest, loving to homeland, willing to sacrifice, creative, honest, independent, and hard work, in order to build the nation and the state better, more prosperous, secure, and peaceful.Â Dewasa ini, di Indonesia terjadi beragam keke-rasan dan degradasi moral yang masih terus terjadi. Fenomena degradasi moral diindikaisikan dengan beragam kekerasan, kriminalitas, penggunaan narkotika, pergaulan bebas, dan berbagai penyimpangan perilaku. Krisis multidimensional dan berbagai kerusakan tersebut pada dasarnya berasal dari harga diri, serta kegagalan dalam pengembangan pendidikan karakter bangsa. Di satu sisi secara esensial Pendidikan IPS bertujuan untuk membangun kemampuan personal, sosial, dan intelektual. Dengan demikian pembelajaran IPS di SMP menjadi sarana dan kesempatan untuk memperkuat karakter siswa, seperti sikap kritis, disiplin, peduli lingkungan, peduli sosial, agama, memiliki minat baca, cinta ke tanah air, rela berkorban, kreatif, jujur, independen, dan kerja keras, dalam rangka membangun bangsa dan negara yang lebih baik, lebih sejahtera, lebih aman, dan damai.Â Â